Alterations of social attention in mental disorders: phenomenology, scope, and future directions for research - Bader, Oren (Consciousness and cognition, 2020)
Mental disorders often involve changes in the way subjects attend to other people. However, the nature of these modifications and how they unfold in different pathologies are not sufficiently clear. This article addresses these issues from the perspective of phenomenological psychopathology. The primary goal of the article is to suggest a new way of assessing and distinguishing the alterations of social attention in subjects with mental disorders. The first part of the article characterizes the essential properties of a capacity for social attention based on multidisciplinary evidence. This model is then used to examine anomalies in social attention in autism, schizophrenia, borderline personality disorder, and social anxiety disorder. The analysis of alterations in the way subjects with different types of pathologies attend to and with others is followed by a threefold typology, which clarifies the phenomenal nature of impairments of social attention in mental disorders.